Penerapan pelaporan sosial pada perusahaan sektor energi yang sudah terdaftar di Bursa Efek Indonesia - Margireta, Ira Anugerah; Khoiriawati, Novi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the company's Corporate Social Responsibility disclosures presented in the Sustainability Report based on the latest reporting standards issued by the Global Reporting Initiative, namely the GRI Standards, and to find out the implementation of the Corporate Social Responsibility (CSR) Report conducted by PT Elnusa Tbk, PT Medco Energy Internasional. Tbk, PT Perusahaan Gas Negara Tbk, PT Adaro Energy Tbk. PT AKR Corporindo Tbk, PT Indika Energy Tbk, PT Energi Mega Persada Tbk, PT Bumi Resources Tbk, PT Super Energy Tbk, and PT Ratu Prabu Energy Tbk. This research uses descriptive qualitative method. Descriptive qualitative is used in this study where the author describes the object of research according to the actual situation by collecting what is needed and related to interpret and compare the results of his analysis of energy sector companies for conclusions. The conclusion is that by using the GRI standards for CSR reporting, the report not only informs the process of implementing CSR, but also informs the wider community about the company's profile and strategy, as well as the management approach taken and other economic benefits.